Capturing patient voice to improve outcomes that matter to patients with desmoid tumor - Kasper, Bernd; Gounder, Mrinal; Hernandez, Lynne; Baumgarten, Christina; Ratan, Ravin (Cancer management and research, 2024)
Desmoid tumors (DT) are rare, intermediate-grade sarcomas characterized by locally aggressive growths that commonly occur intra-abdominally, in the abdominal wall, or in the extremities. Desmoid tumors are 2-3–fold more common in females than males, with most patients aged < 40 years at diagnosis. Clinical course of DT is highly variable but rarely fatal, with median overall survival > 80% at 20 years. However, patient morbidity and DT symptom burden can be high. DT significantly reduce patient quality of life, imposing substantial physical, emotional, and social burdens. Pain, fatigue, and insomnia are common symptoms; disfigurement, mobility restrictions, and, rarely, the need for amputation may also result. Despite its limited impact on survival, patients with DT may have anxiety and depression levels commensurate with those associated with malignant sarcomas. Thus, DT impose an array of significant, long-term morbidities on a young patient population. In order to evaluate the impact of these morbidities, patient-reported outcome (PRO) tools are used, which assess outcomes of importance to patients that extend beyond traditional oncology endpoints. General or oncology-related PROs can be used; although currently, the only DT-specific, validated PRO measure is the GOunder/Desmoid Tumor Research Foundation DEsmoid Symptom/Impact Scale (GODDESS©), consisting of an 11-item DT Symptom Scale (DTSS) and a 17-item DT Impact Scale (DTIS). DTSS and DTIS were secondary endpoints in DeFi, a randomized phase 3 trial of nirogacestat; blinded, pooled data from DeFi were used to validate GODDESS reliability and responsiveness as a PRO measure in DT. Another DT-specific PRO measure, the Desmoid-Type Fibromatosis Quality of Life (DTF-QoL) questionnaire, has been developed but not validated. As novel DT therapies continue to be developed, incorporating DT-specific PRO measures into clinical trials will be key to capturing patient voice, improving outcomes of importance to this unique patient population, and assisting patients and providers in selecting optimal treatment.